PENDAMPINGAN KELOMPOK TANI PADA AGROWISATA SALAK DI DESA SIBETAN BERBASIS PRODUK UNGGULAN DAERAH - Sukanteri, Ni Putu; Lestari, Putu Fajar Kartika; Pratiwi, Luh Putu Kirana; Susanti, Ida Ayu Made; Amaral, Ni Putu Anglila; Budiasa, I Made (Universitas Mataram, 2024)
Sibetan Village agrotourism has been open since 2003, but the hope is that tourists coming to Sibetan Village can increase the selling power of salak. In fact, tourists who visit agrotourism are not yet optimal consumers of the salak produced in Sibetan Village, so the salak produced during the main harvest cannot yet be fully marketed. . This condition requires assistance to groups in supporting agrotourism, especially strengthening human resources in Sibetan Village. The service was carried out in Sibetan Village, Banyakdem District, Karangasem Regency. Service is carried out using several methods, namely: Socialization, Training, Mentoring, Evaluation, Follow-up. The service involves 5 groups engaged in the production and marketing of salak fruit in Sibetan Village, these groups include: Dukuh Lestari Group, Kerta Semaya Group, Werdi Guna, Mekar Sari. The total number of group members is 118 people. The service activities showed that there was a change in the knowledge of group members in the field of marketing salak fruit, packaging and hygiene of products marketed in agro-tourism areas. Assistance provided to farmer groups in Sibetan Village shows that there has been a change in the group's skills in marketing products using online media, packaging salak and product hygiene reaching 80%. This is due to several obstacles faced by group members, such as their weak mastery of technology in using Android. There are not many properties for packaging snake fruit in Sibetan Village, and product hygiene is not commonly carried out during the snake fruit harvesting process. So further assistance is needed to overcome the obstacles faced by the group.